MENINGKATKAN KETERAMPILAN MENGOLAH DAGING SAPI MENJADI BAKSO MELALUI METODE LATIHAN DENGAN PENDEKATAN KETERAMPILAN PROSES BAGI ANAK TUNARUNGU DI SMPLB KOTO BARU KABUPATEN SOLOK - Kasijan, Zulmiyetri, Mega Iswari (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is motivated inability of deaf children have not mastered the skills to process beef into meatballs, so it needs to be taught and trained. This study aims to improve children's skills in processing beef into meatballs through skills training methods to approach the process. Training methods with process skills approach is a teaching method that shows how the process of something being done with children. This type of research is a class act (classroom action research) is conducted in the form of collaboration with colleagues. Subject of two deaf children eighth grade and one teacher. Data obtained through observation, tests and documentation. Then analyzed qualitatively and quantitatively. Based on the results of the study, the child's ability to process beef meatballs child can be increased through training methods with process skills approach. In cycle I've seen the ability to reach FA reached 71.43% and 64.28% TW. the second cycle of the child's ability to process beef into meatballs getting visible increase. This can be proved by the results of 85.71% FA and TW 75%. It can be concluded that the training methods with proven process skills approach can improve the ability of children with hearing impairment in processing beef into meatballs.